Role of Multimedia in Education - Mukherjee, Sukhendu (Edelweiss Applied Science and Technology, 2018)
This can present a challenge to educators wishing to engage students in the classroom while still providing required content in order to enhance learning outcomes. In Teaching and learning communication skills, we have a lot to choose from the world of technology: TV, CD Rom, Computers, the Internet, Electronic Dictionary, Email, Blogs and Audio Cassettes, Power Point, Videos, DVD’s or VCD’s. The last two decades have witnessed a revolution due to onset of technology, and has changed the dynamics of educational institutes, and has also influenced the educational system and the way people interact and work in the society. This rapid rising and development of information technology has offered a better pattern to explore the new teaching model. Using multimedia to create a context to teach communication skill has its unique advantages. As a result technology plays a very important role in teaching communication skill.